Erimielisyydet ryhmämuotoisessa pariterapiassa sekä terapeuttien ja ryhmäläisten vastaukset - Mäkipää, Liina; Joukainen, Reetta (2024)
In a relationship, a couple can have disagreements and communicate negatively by arguing. Emotion-focused couple therapy (EFT) emphasises the importance of emotions and changes a couple's communication habits. Thus, it can be helpful in processing disagreements. In this thesis, we examined what themes are present when couples talk about their differing views and disagreements and how therapists and other participants respond to them. Our data consisted of recorded sessions in couple group therapy. In our data, couples disagreed on topics related to child rearing, communication, conflict situations, alcohol use, meaning of friendship, and sexuality. Therapists responded to these by asking for more information, repeating or rephrasing, offering interpretation, asking what the spouse feels or thinks, and including another couple into the conversation. There were less responses from other participants and these were about shared experiences, differing opinions or mediating comments. Couples differed in the topics of disagreements and how much they expressed them. The most common disagreements related to communication and child rearing. Therapists aimed at increasing spouses' understanding of each other and other participants offered peer support and normalised relationship challenges. Our results broaden understanding of group couple therapy but more research is needed.